The work irregular immigration from outside - Solé, Carlota (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The article presents data on the situation of the undocumented immigrants who took advantage of the process of regularization of 1991, estimates of their presence in the black economy and their difficulties in employment. As a reflection, it analyses the way in which present legislation on immigrants can condition their being labelled as irregulars.